Redescription of both Goniogryllus bistriatus Wu & Wang, 1992 and Callogryllus yunnanus Wu & Zheng, 1992 (Orthoptera: Gryllidae, Gryllinae) - Dai, Jin-Hong; Wang, Rui; Jing, Kai; Ma, Li-Bin (Zootaxa, 2023)
Goniogryllus bistriatus Wu & Wang, 1992 was described at the end of the last century, based on the female holotype, and there have been no further studies or reports related to this species since then. Callogryllus yunnanus Wu & Zheng, 1992 also has a similar situation. Although the holotype is a male, its external genitalia have been lost. These issues pose obstacles to subsequent taxonomic research. Recently, we have successively discovered these two species in Huize County, Yunnan Province, China. To address the aforementioned taxonomic problems, this article describes the male specimens of the G. bistriatus and redescribes the female; meanwhile, since the original description of C. yunnanus lacked male genital characteristics, and we have also conducted a complete redescription of this species based on the new specimen.